Determinan Perilaku Pencegahan Penularan Covid-19 pada Ibu Hamil - Almadani, Safira; Azinar, Muhammad (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Puskesmas Kalimanah has the highest confirmed cases of Covid-19 pregnant women in Purbalinggaa Regency, namely 72 cases (13.01%). Based on the results of a preliminary study to 10 pregnant women, it was found that 80% didn’t use masks when traveling short distances, 90% didn’t wash their hands for at least 20 seconds, and 50% didn’t keep their distance. This study was conducted to find out what factors can influence the behavior of preventing Covid-19 in pregnant women in Puskesmas Kalimanah. Methods: This type of research is quantitative observational analytic with a cross sectional research design. The total population is 235. The samples is 78 pregnant women taken by purposive sampling technique. Questionnaire research instrument. Univariate and bivariate analysis with Chi Square test. Results: The results showed that knowledge (0.001), attitude (0.012), education level (0.004), gestational age (0.000 and 0.037), husband's support (0.014), perceived vulnerability (0.005), perceived severity (0.007), perceived barriers (0.003), and cues to action (0.013) related to Covid-19 prevention behavior in pregnant women in the work area of ​​the Kalimanah Health Center. While the variables of employment status, access to health information, support from health workers and perceptions of benefits were not related to Covid-19 prevention behavior in pregnant women in Puskesmas Kalimanah (p > 0.05). Conclusion: There is a relationship between knowledge, attitudes, education level, gestational age, husband's support, perception of vulnerability, severity, barriers and cues to action with Covid-19 prevention behavior in pregnant women in Puskesmas Kalimanah.